The Effect of Bangun-Bangun Leaves and Lemon on Increase in Babies' Weight - Limbong, Ine Christiani; Putri, Noviyati Rahardjo; Maulida, Luluk Fajria; Argaheni, Niken Bayu; Wahidah, Nurul Jannatul (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2026)
Background: Insufficient breast milk production remains a major barrier to successful exclusive breastfeeding and may negatively affect infant weight gain. Therefore, efforts to enhance lactation using natural galactagogues are needed. Bangun-bangun leaves (Plectranthus amboinicus) are traditionally believed to increase breast milk production. Objective: This study aimed to examine the effect of bangun-bangun leaves combined with lemon on infant weight gain. Methods: quasi-experimental study with a posttest control group design was conducted among 30 breastfeeding mothers. The intervention group (n = 15) received bangun-bangun leaves combined with lemon in the form of brewed tea (200 ml/day) for 14 days, while the control group (n = 15) received no intervention. Moderating variables reflecting breast milk adequacy and the primary outcome was infant weight change, categorized as weight gain or no weight gain. Data were analyzed using Fisher’s exact test due to the categorical data and small sample size.. Results: The analysis showed a statistically significant effect of the intervention on infant weight gain (p = 0.04). All infants (100%) in the intervention group experienced weight gain, whereas 33.3% of infants in the control group showed no weight gain. Conclusion: The combination of bangun-bangun leaves and lemon may serve as a potential natural galactagogue to support breast milk production and promote infant weight gain. These findings provide preliminary evidence supporting the use of bangun-bangun leaves combined with lemon as a natural and accessible intervention to improve breastfeeding outcomes, although further studies with larger samples and objective measurements are needed.